2012
DOI: 10.1149/2.075204jes
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Electroreduction on PtCo3, PtCo and Pt3Co Alloy Nanoparticles for Alkaline and Acidic PEM Fuel Cells

Abstract: Pt-Co alloy nanoparticles have emerged as one of the most promising electrocatalysts for the oxygen reduction reaction (ORR) in hydrogen fuel cells. Our study presents a comprehensive structural, compositional and electrochemical characterization linked with ORR activity for carbon supported PtCo 3 , PtCo, and Pt 3 Co alloy nanoparticle catalysts in 0.1 M HClO 4 and 0.1 M KOH. Surface-sensitive cyclic voltammetry was used to investigate the changes of composition of outermost atomic layers of Pt-Co alloys. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
119
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(133 citation statements)
references
References 92 publications
(134 reference statements)
12
119
0
2
Order By: Relevance
“…This reduction was previously reported in a study of the particle size and alloying effects on Pt-based alloy catalysts, and a relationship between the specific activity and both the Pt surface area and the Pt-Pt bond distance was found [60]. In Table 3, the data of particle size and activity for Pt alloys in alkaline media reported elsewhere and this study are shown [16,31,42,61]. The mass activity for Pt-Co reported in Table 3 is 13.78 mA mg -1 comparing this value with the Pt-black used for PEM fuel cells as 100 at.%; the former has a 77 % of performance.…”
Section: Orr Measurementssupporting
confidence: 80%
See 1 more Smart Citation
“…This reduction was previously reported in a study of the particle size and alloying effects on Pt-based alloy catalysts, and a relationship between the specific activity and both the Pt surface area and the Pt-Pt bond distance was found [60]. In Table 3, the data of particle size and activity for Pt alloys in alkaline media reported elsewhere and this study are shown [16,31,42,61]. The mass activity for Pt-Co reported in Table 3 is 13.78 mA mg -1 comparing this value with the Pt-black used for PEM fuel cells as 100 at.%; the former has a 77 % of performance.…”
Section: Orr Measurementssupporting
confidence: 80%
“…The different conditions, preparation method, particle size, composition, and catalyst loading make rather difficult a comparison; however, for PtCo prepared in this study and considering those parameters, it can be concluded that its performance is in between of Refs. [16,31,42].…”
Section: Orr Measurementsmentioning
confidence: 99%
“…The ORR activity is also affected by the pH and leads to different mechanism in acid and alkaline media 49 . In acidic media, nanoparticle size effect has an important role in increasing the electrochemical surface area, thus increasing the catalytic activity, but in alkaline media, only negligible changes were due to nanoparticle size effects 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…To study the effect of composition on catalytic activity, Strasser's group used an impregnation method to prepare a series of high-surface-area carbon-supported Pt− Co alloy nanoparticle catalysts with atomic ratios of 1:3, 1:1, and 3:1. 175 After electrochemical treatment in 0.1 M HClO 4 , the Pt-based mass activities increased 5-fold from Pt/C to Pt 1 Co 3 /C in the order of Pt/C < Pt 1 Co 1 /C < Pt 3 Co 1 /C < Pt 1 Co 3 /C, with similar particle sizes of 3−4 nm. Using electrochemical dealloying, Strasser's group also studied a series of PtM 3 /C systems with different metals as the second alloy elements (M = Cu, Co, and Ni).…”
Section: Effect Of Composition On Orr Activitymentioning
confidence: 96%